Enhancing patient involvement through shared decision-making: Are we there yet in multiple myeloma? Findings from a cross-country survey - Charlotte Verbeke; Jolien Broekmans; Elise Schoefs; Silène ten Seldam; Kate Morgan; Katie Joyner; Eilidh Duncan; Ariel Aviv; Varda Shoham; Michel Delforge; Anneleen Vanhellemont; Rosanne Janssens; et al. (PLOS One, 2026)
Introduction Shared decision-making (SDM) can enhance patient involvement in treatment and care decisions. Still, questions remain on how multiple myeloma (MM) patients perceive and evaluate their current and desired roles in these decisions and whether characteristics influence their willingness to be involved. This study aimed to identify I) the current knowledge of the concept SDM among MM patients and healthcare professionals (HCPs) involved in MM care, II) how MM patients are and want to be involved in decisions, and III) differences in the willingness to be involved in view of participants’ characteristics (e.g., age, gender, health literacy). Methods An online survey for MM patients and HCPs involved in MM care was launched in October and December 2023, respectively. The data was statistically analyzed. Results 558 patients and 89 HCPs completed the survey. Most patients lived in the Netherlands (28.7%), Israel (23.5%) and Belgium (15.8%), and most HCPs lived in France (39.3%) and Israel (24.7%). 56.6% of the patients and 28.1% of the HCPs had not previously heard of SDM. Almost all patients (96.1%) indicated wanting to be involved in treatment decisions. 3.9% of patients indicated not wanting to be involved, because they did not know whether they would have enough knowledge to decide or because they were used to the HCP deciding. All HCPs believed that MM patients should be involved if they want to. Patients had higher involvement scores at recent consultations and desired to be more involved in initial decisions following diagnosis. The survey revealed no significant differences in participants’ involvement and their characteristics. Conclusion MM patients want to be involved in decisions and HCPs are willing to involve MM patients. However, challenges remain concerning the practical implementation of involvement and SDM. This highlights the importance of understanding SDM and patient involvement and assessing the individual needs and preferences of MM patients.